The Effect of Self Confidence on Student’s Psychomotor Skill in Physical Education Learning - Nuuri Hasan; Slamet Junaidi; Wing Prasetya Kurniawan (CV. Nusantara Sporta, 2023)
This study aims to determine the effect of self-confidence with psychomotor students on physical education learning. The background of this research is based on the results of observations made at SMKN 1 Kediri. The result is that there is a lack of confidence in practicing the techniques that the teacher has taught. This lack of confidence affects and also limits students' space for movement during the implementation of physical education learning. The research uses a quantitative approach with correlational research techniques (relationships). The data collection instrument in this study was by disseminating questionnaires and psychomotor observations in schools. The study took samples using probality samling techniques with a type of simple random sampling of 20% of 300 respondents with a total sample of 60 respondents. Based on the results of the study showed that it was known that the value of Tcalculate 5.124 > Ttable 1.622 with a significance level of 0.000 < 0.05. And it shows a determination value (R Square) of 0.312. Which means that the magnitude of the Self Confidence variable affects the Psychomotor variable by 31.2%, the rest is influenced by other factors. Therefore, there is a significant influence between variable X and variable Y. With the regression model used to predict participation,